THE COLLAPSE OF EFFECTIVE GOVERNANCE: MACAU'S SIN FONG GARDEN AS A CASE STUDY - Mei, Xingwei; Jianhua , Chen (Top Journal of Public Policy and Administration (TJPPA), 2023)
Governance was proposed as a reform to deal with government failures and market failures. However, governance can also fail. This paper analyzes the failure of governance in modern society using Macau Sin Fong Garden as an example and proposes recommendations. The paper explores the concept of governance and its development, including the diversification and management of governance, emphasis on communication and interaction during the governance process, and joint responsibility of governance. The paper also examines the potential constraints of governance, including the fundamental dynamism of capitalism, integration of self-organization into the political system, and the essence of governance as a process of self-organization. The analysis of governance failure is discussed in terms of the effectiveness of the governance framework, the identification of responsibilities, and the ability of actors involved in governance. The paper highlights the importance of a well-established legal system and the need for clearly defined responsibilities in the governance system. The paper concludes that the capability of actors involved in governance is a prerequisite for implementing the governance framework